Usborne Phonics Readers : Frog On A Log - Russell Punter (London, United Kingdom Usborne Publishing Ltd, 2006)
This is a story with a phonics-based text, designed to help children learn to read. Some pages have fold-out flaps which give new readers a chance to guess what will happen next.
Keywords: PY - Language